Cooling tower fog harvesting in power plants – A pilot study. (September 2015) - Ghosh, Ritwick; Ray, Tapan K.; Ganguly, Ranjan
Abstract: Fresh water shortage is a major global problem of this century. Estimates have shown that a large part of the human population will not have access to clean drinking water in a couple of decades from now. Collection of fog can be a useful solution to this concern. Fog, a large source of potable fresh water, has potentials to substitute traditional sources. Attempts have been made over the last few decades to capture fog from nature by installing large fog water collectors along coastal mountains and highlands. However, fog harvesting from artificial fog generators were not envisaged in these studies. In this pilot study, we have explored the possibilities of fog capture from CT (cooling tower) plume in a thermal power plant; CT plume accounts for one of the major sources of industrial water losses. Our study shows that a recovery of about 40 percent water from the drift loss – amounting to a saving of nearly 10.5 m 3 of water per hour from a 500 MW unit – could be achieved using the proposed fog harvesting strategy. Unlike the natural fog harvesting schemes where the fog laden flow is predominantly horizontal, fog flow stream in a cooling tower rises against the gravity. Three parameters are found to influence the collection efficiency predominantly: the shade coefficient of the mesh, effective dripping length of water droplets along the fog net, and angle of inclination of the mesh with respect to the vertically rising fog stream. The observed collection efficiency is more than twice as compared to those of other globally operational fog collectors. Results offer the design bases for full-scale fog harvesting systems that can be deployed in power plant cooling towers and a wide range of other artificial fog generators. Highlights: Pilot study on fog harvesting from cooling tower plume in thermal power plant. Deploys tilted metal wire meshes to trap entrained water droplets from a vertically rising fog stream. Describes the effects of mesh geometry, shade coefficient and mesh clogging on collection rate. Collection rate decreases with mesh inclination angle with the vertical. Water collection rate exceeds the data reported in atmospheric fog harvesting projects by more than 100%.